Pengaruh ROI, ROE, dan Tobin’s Q terhadap Volume Perdagangan Saham pada Perusahaan Sektor Teknologi - Jaudah, Jihan Fadhilah Hang (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to examine the effect of Return on Investment, Return on Equity, and Tobin’s Q on stock trading volume in technology-sector companies listed on the Indonesia Stock Exchange during the 2020–2022 period. This research employs an associative quantitative approach using secondary data obtained from company financial reports published on the Indonesia Stock Exchange. The sample was selected using purposive sampling based on companies that met the research criteria, resulting in 75 firm-year observations. Data were analyzed using Structural Equation Modeling-Partial Least Squares with SmartPLS 4.0. The results show that Return on Investment, Return on Equity, and Tobin’s Q do not have significant effects on stock trading volume. The coefficient of determination indicates that the three variables explain only a very small proportion of the variation in stock trading volume, suggesting that other factors outside the model may have a greater influence on trading activity in technology-sector companies.